Persepsi Guru Mengenai Penggunaan Pembelajaran Daring WAG Terhadap Pencapaian Tujuan Pembelajaran IPS Sekolah Dasar di Tengah Pandemi Covid-19 (Penelitian Deskriptif Kualitatif Pada Guru Kelas Tinggi SDN Pasarean Kecamatan Sumedang Selatan) - Priyatin, P.; Kurnia, Dadang; Karlina, Dety Amelia (Jurnal Pena Ilmiah, 2021)
After the government issued a new policy, there were approximately 68 million students studying from home. Based on study, that in the implementation of online learning in elementary school, most teachers use WAG. In the implementation of this, of course raises a teacher’s perception of obstacle and others. So that this study focuses on the teacher’s perception of the use of WAG in achievening social studies learning objectives. By using descriptive qualitative research methods and data collection tools interviews and observation.For the results of the teacher’s perception research related to the application of online learning. The reason of the teacher’s use WA is because it is familiar and students can already operate it. However, with this policy of course, there are obstacles to be faced, including difficulties for teachers in conveying learning to studies so to measure achievement of studies learning objectives, it is still not optimal.